دور ابعاد اخلاقيات القيادة الادارية في تعزيز التنمية المستدامة: دراسة استطلاعية لآراء عينة من القيادات الادارية في جامعة كركوك - مظفر احمد حسين; احمد عبدالله دانوك; مثنى سعد ياسين (PROSPECTIVE RESEARCHES, 2023)
The research aims to define the role of administrative leadership ethics dimensions in promoting sustainable development, and its main problem is: Does administrative leadership ethics have a role in promoting sustainable development? And his hypotheses were built on the basis of the existence of correlations and influences between the dimensions of administrative leadership ethics and the promotion of sustainable development. The University of Kirkuk was chosen as a study society, and the administrative leaderships working with a sample of (30) respondents were adopted, and the descriptive analytical approach was adopted in achieving its procedures because it is compatible with the nature of the phenomenon studied, and the questionnaire was used In collecting data on the research problem and its objectives, a set of conclusions were reached, the most important of which are: The role of administrative leadership ethics and a significant impact in promoting sustainable development by organizations of all kinds On its basis, a set of proposals were proposed, the most important of which are: To achieve sustainable development, organizations should adopt administrative leadership ethics according to objective foundations and specific regulations upon which to achieve this development.